Optimization and Kinetics of Zirconium Oxychloride (ZOC) Dissolution Using HNO3 - Maria Veronika Purwani; Muzakky Muzakky (Universitas Gadjah Mada, 2019)
The design of chemical reactor can not be separated from the optimization data and reaction kinetics obtained from the experimental measurement. Through the idea of making the dissolution reactor design, the purpose of this research is to obtain optimization data and dissolution kinetics of Zirconium Oxide Chloride (ZOC) using HNO3. The design of the solvent reactor is required to make the feedstock in the liquid-liquid extraction process continuously. The extraction process is a mini-pilot plant unit as a nuclear-grade zirconia manufacture. The dissolution optimization was carried out by dissolving ZOC solids of zircon sand processed products using HNO3 in a container with some variation of contact time, HNO3 concentration and temperature. While the kinetics data was gained by extracting from the optimization data obtained based on the formula of reaction orders. The investigation result with 6 gr of ZOC and 6M HNO3 concentration obtained the best contact optimum time of 2 minutes and the conversion number (α) of 0.96. The dissolution reaction mechanism was estimated in accordance with the reaction of order 1 with the k value of 1.5879 minutes-1. It was predicted that the reaction mechanism of ZOC dissolution in HNO3 begins with diffuse control and is followed by chemical reaction control. With increasing conversion temperature, the conversion will increase to 0.98, while the reaction also follows the reaction order 1. The optimum temperature at 60 °C, and the correlation between temperature (T) with the calculated reaction rate constant (k) according to the Arrhenius formula yielded an equation of ln k = - 4191,6 / T + 13,903 or k = 13,903.e- 4191,6 / T, with the frequency factor A = 1091430 and the activation energy E = 34,848 kJ / mole.